Application of Saliva as Diagnostic Bio-Fluid- An Overview - Rathee, Manu; Bhoria, Mohaneesh (Journal of Diagnostics, 2014)
Saliva, a biologic fluid, recently has been a boon in the field of diagnostic science, as the presence of viable biomarkers in saliva elaborate its applications in multiplexed assays, disease diagnosis, clinical monitoring and for clinical decisions of patient care. Application of saliva in diagnosis is undeniable as ease in sample collection and conventional procedure. This article provides emerging evidence to provide an overview of salivary diagnostics in various fields of diagnosis and affirm its application as diagnostic Bio-Fluid.